5-Fluorouracil Impairs Transmission of Acetylcholine in the Hippocampus and Induces Cognitive Impairments in Mice - Huang, Xiwen; Peng, Shunqing; Lan, Yongquan; Chen, Wenjun; Wu, Jianlin (Journal of integrative neuroscience, 2025)
Background: Chemotherapy-induced cognitive impairments are a significant adverse sequela of cancer treatment. The potential mechanism of chemotherapy-induced cognitive impairments remains elusive. The present study evaluated the impact of a commonly utilized chemotherapy agent, 5-fluorouracil (5-FU), on acetylcholine (ACh) levels in the hippocampus. Methods: 5-FU was injected into mice once a day for 10 days to create a mouse model of chemotherapy-induced cognitive impairment. Microdialysis and HPLC-MS/MS were used to determine hippocampal ACh levels. Biocytin injection and patch-clamp recordings were performed on cholinergic (ChAT) neurons in the medial septum (MS) to observe their morphological and electrophysiological changes. Chemogenetic tools were used to activate ChAT neurons in the MS. The acetylcholinesterase inhibitor donepezil was injected i.p. into mice to elevate ACh levels in the brain. Results: Cognitive performance in mice was impaired after 5-FU treatment, accompanied by reduced ACh release in the hippocampus. The administration of 5-FU led to compromised structural integrity and diminished activity of ChAT neurons in the MS. Chemogenetic stimulation of MS ChAT neurons ameliorated the cognitive impairments. The administration of donepezil also reduced the cognitive impairments caused by 5-FU. Conclusions: 5-FU therapy caused cognitive impairments in mice by affecting the neuronal structure and activity of ChAT neurons in the MS. Inducing the increase of ACh levels could be a promising therapeutic approach for addressing 5-FU treatment-induced cognitive impairments.